1995
DOI: 10.1259/0007-1285-68-807-296
|View full text |Cite
|
Sign up to set email alerts
|

Radiation dose reduction in paediatric fluoroscopy using added filtration

Abstract: Studies on a water phantom indicate that the insertion of extra tube filtration combined with the removal of the antiscatter grid can reduce the total energy imparted from paediatric fluoroscopy by a factor of more than four when automatic exposure control is used. The omission of the grid is responsible for up to 40% of the reduction while the addition of 0.7 mm steel filtration is found to account for a further reduction in energy imparted of between 57% and 70%, for depths of water simulating small patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
19
0

Year Published

1997
1997
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 6 publications
1
19
0
Order By: Relevance
“…Added filtration together with a removal of the grid was found to reduce the dose a factor of 4 when automatic exposure control was used. The image quality reduction was considered to be small and the loss of diagnostic information unimpaired [11]. Potential dose savings of up to 85% were found when using carbon fibre cassettes, modern image intensifier, increasing film-screen sensitivity, collimation and higher kilovoltage in radiographs [12].…”
Section: Introductionmentioning
confidence: 99%
“…Added filtration together with a removal of the grid was found to reduce the dose a factor of 4 when automatic exposure control was used. The image quality reduction was considered to be small and the loss of diagnostic information unimpaired [11]. Potential dose savings of up to 85% were found when using carbon fibre cassettes, modern image intensifier, increasing film-screen sensitivity, collimation and higher kilovoltage in radiographs [12].…”
Section: Introductionmentioning
confidence: 99%
“…A similar investigation has recently been published by Nicholson et al [2] who measured the dose reduction Abstract. Paediatric double-contrast barium enema examinations are usually performed at high tube voltage, 102-105 kV.…”
Section: Introductionmentioning
confidence: 59%
“…The equipment is mainly used for examinations of the abdomen and bladder and offers the possibility to select the beam filtration in four steps by adding different thicknesses of copper (Cu) during both fluoroscopy and fluorography. Previous studies of suitable materials for spectral shaping have shown that Cu is a good choice compared with K-edge filters regarding both image quality, tube loading, dose reduction and price [3,8,9].The aim of this study was to investigate how much the effective dose could be reduced when adding Cu filter in the beam for a colon examination, and if this dose reduction could be achieved without endangering the image quality needed for accurate diagnosis.A similar investigation has recently been published by Nicholson et al [2] who measured the dose reduction Abstract. Paediatric double-contrast barium enema examinations are usually performed at high tube voltage, 102-105 kV.…”
mentioning
confidence: 59%
See 1 more Smart Citation
“…To this end, numerous authors over a number of years have recommended removing the antiscatter grid from the X‐ray beam during fluoroscopic examinations of small children 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 . While some authors have quantified the reduction in patient dose to these pediatric patients, 7 , 13 , 16 , 17 , 18 , 19 the loss of image quality associated with this reduction in patient dose has been measured only on a limited basis 7 , 9 , 14 , 16 , 17 , 20 with phantoms as opposed to live models.…”
Section: Introductionmentioning
confidence: 99%